Case Report Unilateral Microphthalmos with Associated Retina Detachment in a Nigerian Child - AK Akinwalere, BO Omolase, CO Omolase, MY Majekodunmi (Pakistan Journal of Ophthalmology, 2018)
This report is that of a two year old Nigerian child who presented to the eye clinic of Federal Medical Centre, Owo in June, 2010 on account of small left eye noticed since birth. Examination carried out revealed no perception of light in the left eye, left microphthalmos with associated retinal detachment. The right eye was normal. Systemic examination did not reveal any associated congenital anomaly. There is no history of similar occurrence in her family but the mother had a febrile illness with associated rashes suspicious of rubella in the course of the pregnancy. Retina surgery was not advised in view of the no perception of light in the affected eye. There is need for adequate antenatal care to prevent some congenital anomalies.